Synthesis of Zeolite from Coal Bottom Ash Using Hydrothermal Method as An Adsorbent for Heavy Metals Cd, Pb, Fe, and Cu - Yayat Setiawan; David Bahrin; Leily Nurul Komariah (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
This study aims to synthesize zeolite from coal combustion bottom ash using the hydrothermal method and evaluate its effectiveness in adsorbing heavy metals—specifically cadmium (Cd), lead (Pb), iron (Fe), and copper (Cu). Bottom ash was treated via alkali fusion at 750°C, followed by acid activation with 1 M HCl to extract silica and alumina. Zeolite synthesis was hydrothermal at 100°C with 6, 12, and 24 hours of crystallization. Sodium aluminate (NaAlO2) was added to adjust the Si/Al ratio and enhance structural stability. The synthesized zeolites were characterized using X-ray Fluorescence (XRF) and Scanning Electron Microscopy (SEM). The sample crystallized for 12 hours and exhibited the highest SiO2/Al2O3 ratio, measuring 3.73. Adsorption tests revealed optimal performance at pH 5–9 and 120 minutes contact time, achieving removal efficiencies of 97.84% for Pb2+, 99.47% for Cd2+, 99.73% for Fe2+, and 99.91% for Cu2+. These findings demonstrate that bottom ash-derived zeolite is a promising, low-cost adsorbent for heavy metal removal from wastewater. It supports use in sustainable and long-term industrial effluent treatment systems.